If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9g+7=4g-13
We move all terms to the left:
9g+7-(4g-13)=0
We get rid of parentheses
9g-4g+13+7=0
We add all the numbers together, and all the variables
5g+20=0
We move all terms containing g to the left, all other terms to the right
5g=-20
g=-20/5
g=-4
| 2x+40=12x-120 | | 4a-3a+6=4a-8 | | 2x-(4+x)=22-x | | 2(7x+7=8 | | 7e-21=19-e | | 10l-47=2l+41 | | 2x+4=5x–8 | | 25-45=-x+10 | | 8x-8=-88 | | 50-13=2x+10 | | 2(2x-5)-5=3x-11 | | 9x+31=2x+45 | | 2g-8=4g+4 | | 5x+7×=43 | | 2x-44=2(2x+2) | | 14+x=2x-3 | | -63-10x=21-3x | | -4x-34=-x-49 | | 12-7p=-9 | | x5=68 | | 12y-17=4y+15 | | 4f+7=15 | | (t-12)/2=13 | | 3n+2n+1=5n+1 | | 10≤2x=x+9 | | 4b-20=15-b | | 7s-9=4s+6 | | 10y-3=78 | | 10-7a=-60 | | 6g-7=4g+5 | | 8r-1=4r-5 | | 5u-8=2u+4 |